2019
DOI: 10.1007/s00726-019-02725-2
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ADMA, urinary ADMA excretion, and late mortality in renal transplant recipients

Abstract: Cardiovascular disease (CVD) is the leading cause of death in renal transplant recipients (RTR). Elevated plasma asymmetric dimethylarginine (pADMA), an endogenous nitric oxide synthase inhibitor produced from the turnover of methylated arginine moieties in proteins, is a risk factor for CVD and mortality. It is unknown how urinary ADMA excretion (uADMA), one of the main ADMA elimination routes, is associated with long-term survival. Furthermore, the association of pADMA and uADMA with markers for turnover of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 55 publications
2
14
0
Order By: Relevance
“…The findings of the present study support the observations of the lower circulating ADMA and SDMA concentrations in black subjects measured in the SABPA study [44]. Low urinary excretion of ADMA is a cardiovascular risk factor in white adults [45,46]. The close comparability of urinary ADMA excretion in the young white and black men of the African-PREDICT study suggests that the black population is not exposed to a higher ADMA-associated cardiovascular risk than the white population, but, again, it should be taken into account that the study included healthy screening normotensives.…”
Section: Arg Dimethylation and Blood Pressuresupporting
confidence: 89%
“…The findings of the present study support the observations of the lower circulating ADMA and SDMA concentrations in black subjects measured in the SABPA study [44]. Low urinary excretion of ADMA is a cardiovascular risk factor in white adults [45,46]. The close comparability of urinary ADMA excretion in the young white and black men of the African-PREDICT study suggests that the black population is not exposed to a higher ADMA-associated cardiovascular risk than the white population, but, again, it should be taken into account that the study included healthy screening normotensives.…”
Section: Arg Dimethylation and Blood Pressuresupporting
confidence: 89%
“…The whole-body asymmetric arginine dimethylation was investigated in adult renal transplant recipients by measuring DMA, the major metabolite of ADMA, in urine by GC–MS (Post et al 2021 ). This study revealed that the whole-body asymmetric arginine dimethylation is associated with all-cause mortality in adult renal transplant recipients and supports the particular role of this PTM in chronic kidney disease (Frenay et al 2015 ; Said et al 2019a , b ).…”
supporting
confidence: 82%
“…High plasma ADMA was correlated with high all-cause mortality and late mortality in renal transplant recipients. In contrary, urinary excretion of ADMA and SDMA is inversely associated with cardiovascular disease (CVD) and all-cause mortality [101]. Exogenous treatment of human monocytoid cells THP-1 with micromolar concentrations of ADMA significantly upregulates the levels of IL-8, TNF-α, MCP-1, chemokine receptors CCR 2 and CXCR 2 , activation of NF-κB, and promotes monocytic binding to human umbilical vein endothelial cells [57].…”
Section: Adma—the Small Molecule Metabolite Product Of Arginine Mementioning
confidence: 99%
“…Although accumulation of plasma ADMA correlates with impaired NO synthesis and contributes to the hypertension and immune dysfunction associated with chronic renal failure, it appears that the (patho)physiological impact of ADMA does not take place in plasma [91]. Plasma arginine concentrations are in the range of ~100 to 200 µM, but the plasma ADMA concentrations are much less, 0.3–1.0 µM at a typical level [54,61,101,104,105,106,107]. Thus, in the circulating bloodstream, ADMA is not competent enough against arginine for receptor binding.…”
Section: Adma—the Small Molecule Metabolite Product Of Arginine Mementioning
confidence: 99%